A multilevel inverter using switched capacitors with reduced components. Issue 17 (22nd January 2021) - Taheri, Asghar; Rasulkhani, Ahad; Ren, Hai‐Peng
Abstract : In this study, a novel multi‐source switched‐capacitor converter is proposed. In the proposed topology, the capacitor charging is carried out in a self‐balancing form eliminating the need for additional balancing circuits. After that, the design principle of the proposed inverter is discussed in details. A comparison study between the proposed topology and other existing topologies is provided next. According to this comparison, the proposed topology requires fewer components, such as DC power supplies, switches, capacitors, and diodes. Further, the simulation results for 15‐level and 127‐level and the experimental results for a 15‐level inverter are provided. The simulation and experimental results are in close agreement and verify each other.